2010
DOI: 10.4141/cjss09029
|View full text |Cite
|
Sign up to set email alerts
|

Soil phosphorus availability in no-till versus conventional tillage following freezing and thawing cycles

Abstract: (1 and 160 kg N ha (1 every 2 yr and were enriched or not with 2 g of soybean residues. Under controlled conditions, the cores were subjected to various FTC treatments, with each cycle consisting of 5 d of freezing and 5 d of thawing. The water-extractable P (Pw) and Mehlich-3 extractable P (P M3 ) contents were higher in soil samples collected in the spring compared with those collected the previous fall. After one and three FTC, Pw values averaged 17.4 mg kg(1 in NT and 7.5 mg kg (1 in CT and were not influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 43 publications
1
33
0
1
Order By: Relevance
“…These observations confirm that residual P fertilizer could affect the dynamics of soil P during the nongrowing season and increase labile P fractions which are easily adsorbed onto AEM (Blake et al 2000;Shi et al 2013). Messiga et al (2010) showed that water-extractable P and P M3 were higher in soil collected in the spring than in soil collected in the previous fall. Resin-P as a P sink pool can also be increased through mineralization, because microbial biomass P is higher in treatments with P fertilization.…”
Section: Nongrowing Season Soil Phosphate As Measured With Anionic Exsupporting
confidence: 72%
See 1 more Smart Citation
“…These observations confirm that residual P fertilizer could affect the dynamics of soil P during the nongrowing season and increase labile P fractions which are easily adsorbed onto AEM (Blake et al 2000;Shi et al 2013). Messiga et al (2010) showed that water-extractable P and P M3 were higher in soil collected in the spring than in soil collected in the previous fall. Resin-P as a P sink pool can also be increased through mineralization, because microbial biomass P is higher in treatments with P fertilization.…”
Section: Nongrowing Season Soil Phosphate As Measured With Anionic Exsupporting
confidence: 72%
“…Freezing and thawing cycles observed during the nongrowing season could also explain the greater AEM-P measured under fertilized NT in comparison with MP (Messiga et al 2010;Cade-Menun et al 2013). Freezing and thawing cycles exert physical abrasive forces on organic materials (Uhlen 1988) and crop residues (Hansen et al 2000), and the disruption of these materials releases dissolved P depending on the exposure to and extent of the freezing and thawing cycles.…”
Section: Nongrowing Season Soil Phosphate As Measured With Anionic Exmentioning
confidence: 99%
“…Messiga et al (2010) used soil cores (0-5 cm) collected from this site in September 2007 and showed that after one and three freeze-thaw cycles, water-extractable P and P M3 concentrations were greater under NT than under MP. In another study considering the long-term impact of tillage practices and P fertilization on soil P status, Messiga et al (2012) used samples collected in 2010 to highlight greater soil test P accumulations in the 0-to 5-cm depth under NT than under MP.…”
Section: Mehlich-3 Phosphorus and Aluminummentioning
confidence: 99%
“…The higher soil phosphorus stocks in the CPS could be explained by the addition of phosphorus fertilizer to the fields (Aguiar et al 2013;Messiga et al, 2013;Costa et al, 2014). Generally, an increase in soil phosphorus is observed after use of P fertilizers in the topsoil due to the low mobility of phosphorus, especially in no-till systems (Costa et al, 2007;Pavinatto et al, 2009;Messiga et al, 2010). In several of the CPS sites, there are crop rotations of maize, rice and soybean, and all these crops are fertilized with phosphorus, especially soybean, because phosphorus is an important nutrient in the biological nitrogen fixation process (Divito and Sadras, 2014).…”
Section: Land-use Changes Alter Nitrogen and Phosphorus Stocksmentioning
confidence: 99%
“…One consequence of this lower phosphorus mobility throughout the soil profile is that when P fertilizers are applied, they tend to increase soil phosphorus concentration on the soil surface, but they also make phosphorus available by loss through the soil erosion process and surface runoff (Messiga et al, 2013). The use of agricultural practices like no-till may further increases phosphorus concentration in the surface soil due to the non-movement of the soil layer (Pavinatto et al, 2009;Messiga et al, 2010Messiga et al, , 2013. Soil phosphorus is also affected by physical characteristics of the soil, such as how the size of soil aggregates influences the extent of soil phosphorus availability to plants (Fonte et al, 2014).…”
mentioning
confidence: 99%